Post-COVID-19 syndrome and its long-term complications: A systematic review (Research, Society and Development, 2024)
The Coronavirus disease-2019 (COVID-19) is a contagious infection caused by the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) that can be transmitted through aerosol droplets from infected people. The most common symptoms of patients with COVID-19 are fever, cough, dyspnea, myalgia, anosmia, and dysgeusia. The pathophysiology of the post-COVID-19 syndrome or chronic phase of SARS-CoV-2 is related to the symptoms of the acute phase and the extent of the "cytokine storm" in the different affected organs. However, despite knowledge of the prevalence of sequelae in COVID-19, the causative mechanisms are not fully understood, and this is the focus of this research. This is a systematic review study conducted in PubMed, SciELO, Embase, and Web of Science databases using Mesh/Decs descriptors and Boolean operators. Post-COVID-19 syndrome is considered a diffuse, multisystemic inflammatory condition that can generate several chronic symptoms. The dissemination of information regarding the consequences of the chronic phase of this syndrome is essential to mitigate the possible sequelae that negatively impact the resumption of functional and occupational activities of these individuals.